Conference procedings: innovations in social marketing third annual - Academy for Educational Development (s.c.: Prspect Associates Westat, Inc, 1997)
Contents: Contraceptive social marketing in Pakistan: a new system for assessing the impact of price increases on condom sales and consumption ina a low-resource setting. Towards an integrated research design for social marketing interventions...The marketing concept and health promotion: a preliminary survey and analysis of 1990's "Health Promotion" literature...Promoting secondary education for women in bangladesh: using a theory-based behavioral elicitation technique to identify salient consequences of enrolling dauhters...A marketing view of behavior management: exploring the exchange process
Keywords: Marketing Social